Becoming "Mediterranean" in Post-socialist Croatia - Škrbić Alempijević, Nevena (2014)
In political discourse, but also in public debates in many EU countries, the Eurozone crisis has often been brought in connection with "the Mediterranean". In those narratives the term is usually used as a reference to the monetary policies of Euro-Mediterranean countries, but also involves what Michael Herzfeld defines as "stereotypical permutations of a civilizational ideal". The intertwinement of the crisis and the concept of Mediterranean is also evoked in contemporary Croatia, where the internal economic instability is justified as a reflection of specific circumstances affecting the whole Euro-Mediterranean region. However, reaching for the Mediterranean imaginary has an additional ideological dimension in Croatia, since it has been a response to another type of crisis. Due to the break-up of Yugoslavia, war and transition from socialism, since the 1990s images of the Croatian state, culture and identity have been created anew. One of the dominant identification strategies has been claiming the country's Mediterranean identity. The Mediterranean has become omnipresent in various social spheres: in political circles, media, tourism industry, within the academic community and so on. The Mediterranean in Croatia has turned into a space shaped by different interpretations, interests, visions of the past and hopes for the future. The aim of this paper is to analyze ways in which various actors use the concept of Mediterranean to address or resolve different crises in their everyday life. The research is primarily based on fieldwork in places branded as "Mediterranean" and on discourse analysis applied to media reports, promotional materials, etc.
ENG